(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Frahtia K, Attar MR, Diabi C. 2022. Diversity and richness of day butterflies species (Lepidoptera Rhopalocera) in the Chettaba Forest, Constantine, Northeastern Algeria. Biodiversitas 23: 3429-3436. In order to balance the lack of data concerning lepidopteran fauna in the region of Constantine (northeastern Algeria), a preliminary inventory has been drawn up in that region. This work was led during the 2021 spring season at the Chettaba Forest, where three stations were chosen: The ’Aleppo pine forest’, the low matorral and the high matorral. Data collection required one outing per week for each site, during which specimens were collected and/or enumerated. A total of 815 specimens from 15 species belonging to 3 families were recorded: Pieridae (6 species), Lycaenidae (5 species), and Nymphalidae (4 species). The low and the high matorrals were the richest stations, with 15 species for the former and 11 species for the latter, but only 10 species were observed in the ’Aleppo pine forest’. The highest centesimal and occurrence frequencies were recorded for Pieris rapae in all three stations. The low matorral proved to be the most diversified station (H´: 3.00 bits) because of an important heterogeneity and quality of the habitat due to the biological post-fire rise that makes it richer in nectar-bearing plants, which is important for butterfly concentration.